Sargassum-to-energy: A review of bioethanol production and its significance in Ghana - Winnie A. Owusu; Solomon A. Marfo; Harrison Osei (Sustainable Environment)
Macroalgal biomass (seaweed) is one of the most abundant and valuable renewable resources globally. Lately, the conversion of this into biofuels has gained considerable attention as an alternative to fossil fuels. In addition, the success in exploiting this feedstock hinges on its distinctive characteristics and the method employed to isolate its specific active components. Within the framework of a circular economy, invasive Sargassum species present themselves as promising candidates for bioethanol production. Ghana’s bioethanol production feedstocks are mostly from edible crops in competition for human consumption or lignocellulosic biomass with high lignin content. This suggests utilisation of this invasive and valuable bioresource is still not recognised in the country. The present communication reviews Sargassum invasiveness (availability), chemical composition, processes and opportunities in bioethanol production in a potential country, Ghana. This aligns with the clean and sustainable energy fulfillment as outlined in Ghana’s energy transition framework policy and SDG 7.